The effect of plaque morphology, material composition and microcalcifications on the risk of cap rupture: A structural analysis of vulnerable atherosclerotic plaques - Corti, Andrea; De Paolis, Annalisa; Grossman, Pnina; Dinh, Phuc A.; Aikawa, Elena; Weinbaum, Sheldon; Cardoso, Luis (Frontiers in Cardiovascular Medicine, 2022)
Background: The mechanical rupture of an atheroma cap may initiate a thrombus formation, followed by an acute coronary event and death. Several morphology and tissue composition factors have been identified to play a role on the mechanical stability of an atheroma, including cap thickness, lipid core stiffness, remodeling index, and blood pressure. More recently, the presence of microcalcifications (µCalcs) in the atheroma cap has been demonstrated, but their combined effect with other vulnerability factors has not been fully investigated. Methods: We performed numerical simulations on 3D idealized lesions and a microCT-derived human coronary atheroma, to quantitatively analyze the atheroma cap rupture. From the predicted cap stresses, we defined a biomechanics-based vulnerability index (VI) to classify the impact of each risk factor on plaque stability, and developed a predictive model based on their synergistic effect. Results: Plaques with low remodeling index and soft lipid cores exhibit higher VI and can shift the location of maximal wall stresses. The VI exponentially rises as the cap becomes thinner, while presence of a µCalc causes an additional 2.5-fold increase in vulnerability for a spherical inclusion. The human coronary atheroma model had a stable phenotype, but it was transformed into a vulnerable plaque after introducing a single spherical µCalc in its cap. Overall, cap thickness and µCalcs are the two most influential factors of mechanical rupture risk. Conclusions: Our findings provide supporting evidence that high risk lesions are non-obstructive plaques with softer (lipid-rich) cores and a thin cap with µCalcs. However, stable plaques may still rupture in the presence of µCalcs.